2020
DOI: 10.12982/cmujns.2021.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Plasma Treatment on Cooking and Physical Qualities of Pigmented Thai Rice

Abstract: Plasma surface modification processes account for most of the commercial uses of surface modification because they are fast, efficient methods for improving the adhesion, wettability properties and other surface characteristics of a variety of materials. This research was aimed to investigate of surface modification of pigmented rice by plasma technique. Two rice varieties namely Kum Doi Saket and Hom Nil rice were used. The samples were subjected to plasma treatment with different gas types to determine suita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
(70 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, it was found that exposure of pigmented rice flour particles to plasma at higher power and longer time caused attacking of the plasma particle on the surfaces; consequently, changed of its morphology (Figure 1). It was found that as plasma power and exposure time were increased, rough surface, cracking and erosion on the rough surface of pigmented rice and starch granules occurred (Chen, 2014;Mir et al, 2016;Noppakun et al, 2021). From the surface quality analysis of plasma treated rice flour samples, more eroded, rough and porous surfaces were observed when compared with the untreated sample.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it was found that exposure of pigmented rice flour particles to plasma at higher power and longer time caused attacking of the plasma particle on the surfaces; consequently, changed of its morphology (Figure 1). It was found that as plasma power and exposure time were increased, rough surface, cracking and erosion on the rough surface of pigmented rice and starch granules occurred (Chen, 2014;Mir et al, 2016;Noppakun et al, 2021). From the surface quality analysis of plasma treated rice flour samples, more eroded, rough and porous surfaces were observed when compared with the untreated sample.…”
Section: Discussionmentioning
confidence: 99%
“…The surface roughness of the grain was clear when using plasmas of argon. Moreover, it was reported that Ar+ in combination with reactive oxygen species such as *OH, *O and *O2 caused epidermis to degenerate guard cells (Noppakun et al, 2021). The highly energetic species produced during the plasma generation bombarded the surface of the starch granule.…”
Section: Discussionmentioning
confidence: 99%
“…Different kinds of plasma technologies were classified as gases (air, nitrogen, helium, argon) and methods (plasma jet, corona discharge, gliding arc discharge, dielectric barrier discharge) to release plasma at atmospheric pressure and low temperature. 1,2 The numerous benefits of plasma treatment included cost-effective running, simply convenient manipulation and environmentally protective friendliness. 2,3 Plasma technology was successfully applied in sterilization of medical equipment, tooth bleaching.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma is mainly consisted of photons, ions, free electrons and atoms generated from corona discharge or dielectric barrier discharge (5,7). Two types of plasma include thermal plasma and non-thermal plasma (8). The most advantages of plasma technology are safe, flexible, cheap (9).…”
Section: Introductionmentioning
confidence: 99%
“…Brown rice treated by direct current gaseous discharge plasma resulted to more water uptake (15). Plasma treatment caused a decrease in cooking duration and improvement in water uptake ratio, length expansion ratio and volume expansion ratio, water absorption of pigmented Thai rice (8). Cold plasma treatment was utilized to enhance cooking quality of basmati rice (16).…”
Section: Introductionmentioning
confidence: 99%